Caught in the cross-fire ; Balancing in a string ; Mitch [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Talks about the military operations against the in Negros killing many civilians in the crossfire ; poverty alleviation and inflation ; and the link of Alma Vaca, Maya Valdez and Mitch Valdez.
Caught in the crossfire (13 min.) -- Balancing on a string (13min.) -- Mitch (15 min.)
VHS.
Keywords: Valdez, Maya; New Peoplpe's Army; Civil rights -- Philippines; Inflation (Finance) -- Philippines; Poverty -- Philippines; Philippines -- Economic conditions